2014
DOI: 10.1186/cc13876
|View full text |Cite
|
Sign up to set email alerts
|

Elevated plasma thrombomodulin and angiopoietin-2 predict the development of acute kidney injury in patients with acute myocardial infarction

Abstract: IntroductionAcute kidney injury (AKI) following acute myocardial infarction (AMI) is associated with unfavorable prognosis. Endothelial activation and injury were found to play a critical role in the development of both AKI and AMI. This pilot study aimed to determine whether the plasma markers of endothelial injury and activation could serve as independent predictors for AKI in patients with AMI.MethodsThis prospective study was conducted from March 2010 to July 2012 and enrolled consecutive 132 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 36 publications
2
40
0
Order By: Relevance
“…Thrombomodulin is shed from activated or damaged endothelial cells, such that circulating sTM likely reflects endothelial dysfunction rather than the anticoagulant activity of membrane‐bound thrombomodulin . Furthermore, our findings are consistent with the limited existing human literature showing the association of sTM, and to a lesser extent protein C, with AKI in critical illness and myocardial infarction populations …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Thrombomodulin is shed from activated or damaged endothelial cells, such that circulating sTM likely reflects endothelial dysfunction rather than the anticoagulant activity of membrane‐bound thrombomodulin . Furthermore, our findings are consistent with the limited existing human literature showing the association of sTM, and to a lesser extent protein C, with AKI in critical illness and myocardial infarction populations …”
Section: Discussionsupporting
confidence: 86%
“…In these models increased levels of the antifibrinolytic protein plasminogen activator inhibitior‐1 (PAI‐1) and reduced levels of the endogenous anticoagulant protein C contribute to microvascular thrombin deposition and impaired tissue perfusion . In nontransplant critical illness and myocardial infarction populations, plasma levels of soluble thrombomodulin (sTM) were recently shown to be associated with AKI . sTM is thought to be a marker of endothelial activation—it derives from the release of membrane‐bound thrombomodulin into circulation when endothelial cells are damaged—and one study in sepsis patients showed that sTM was superior to other markers of endothelial injury for predicting AKI .…”
Section: Introductionmentioning
confidence: 99%
“…Genetic polymorphisms in the ABO gene have been associated with circulating levels of glycoproteins important in endothelial function and inflammation, including soluble intercellular adhesion molecule-1 (ICAM-1), thrombomodulin, vWF, and the selectins (12,(20)(21)(22)(23). These same proteins have been implicated in the pathogenesis of AKI (24)(25)(26)(27)(28). Although non-O blood types are reported risk factors for MI, VTE, and ARDS, it is unknown if ABO blood type is associated with AKI risk (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with multi‐vessel ischemic heart disease have significantly higher level of sTM than those without . Ang‐2 and sTM can serve as independent clinical predictors of the development of AKI in patients with acute myocardial infarction …”
Section: Soluble Thrombomodulinmentioning
confidence: 99%
“…23 Ang-2 and sTM can serve as independent clinical predictors of the development of AKI in patients with acute myocardial infarction. 24…”
Section: Soluble Thrombomodulinmentioning
confidence: 99%